An Analysis of Meng-Prefixation on English Loan Words in Indonesian Language From Morpheme Based Model Perspective - Dharma Susena Suyasa, Made; Damayanthi Muliawan, Made Sani (International Seminar on Austronesian Languages and Literature, 2021)
Word formation rules of affixation on loan words in Indonesian langugae is not completely described. This research is aimed at describing word formation rules of meng- prefix on English loan words. The data in this article was gathered by observing everyday conversations by Indonesian native speakers around the writer. The meng- prefixation process on the data were tested and described based on morpheme based model. Based on the analysis, it is found that the rules of word formation for meng- prefix need to be redifined. It is also found that some allomorphs of meng- prefix are more productive than its other allomorphs. The source of data in this paper was some conversations by Indonesian native speakers. The data were gathered by observing the conversations. Based on the techniques, the writer found 20 loand words from English. However, the most frequent loan words are only five, namely WA, SMS, FB, IG, and Twit. Actually, the loan words had undergone some word formation process, namely abreviation process. In this paper, the abriviation process is not the focus. The focus in this paper is the affixation process on that five loan words. All alomorphs of meng- prefix are tested on the loan words